Spatial-temporal variations in surface ozone over Ushuaia and the Antarctic region: observations from in situ measurements, satellite data, and global models - Nadzir, Mohd Shahrul Mohd; Ashfold, Matthew J.; Khan, Md Firoz; Robinson, Andrew D.; Bolas, Conor; Latif, Mohd Talib; Wallis, Benjamin M.; Mead, Mohammed Iqbal; Hamid, Haris Hafizal Abdul; Harris, Neil R.P.; Ramly, Zamzam Tuah Ahmad; Lai, Goh Thian; et al. (Springer Verlag (Germany), 2018)
The Antarctic continent is known to be an unpopulated region due to its extreme weather and climate conditions. However, the air quality over this continent can be affected by long-lived anthropogenic pollutants from the mainland. The Argentinian region of Ushuaia is often the main source area of accumulated hazardous gases over the Antarctic Peninsula. The main objective of this study is to report the first in situ observations yet known of surface ozone (O 3 ) over Ushuaia, the Drake Passage, and Coastal Antarctic Peninsula (CAP) on board the RV Australis during the Malaysian Antarctic Scientific Expedition Cruise 2016 (MASEC’16). Hourly O 3 data was measured continuously for 23 days using an EcoTech O 3 analyzer. To understand more about the distribution of surface O 3 over the Antarctic, we present the spatial and temporal of surface O 3 of long-term data (2009–2015) obtained online from the World Meteorology Organization of World Data Centre for greenhouse gases (WMO WDCGG). Furthermore, surface O 3 satellite data from the free online NOAA-Atmospheric Infrared Sounder (AIRS) database and online data assimilation from the European Centre for Medium-Range Weather Forecasts (ECMWF)-Monitoring Atmospheric Composition and Climate (MACC) were used. The data from both online products are compared to document the data sets and to give an indication of its quality towards in situ data. Finally, we used past carbon monoxide (CO) data as a proxy of surface O 3 formation over Ushuaia and the Antarctic region. Our key findings were that the surface O 3 mixing ratio during MASEC’16 increased from a minimum of 5 ppb to ~ 10–13 ppb approaching the Drake Passage and the Coastal Antarctic Peninsula (CAP) region. The anthropogenic and biogenic O 3 precursors from Ushuaia and the marine region influenced the mixing ratio of surface O 3 over the Drake Passage and CAP region. The past data from WDCGG showed that the annual O 3 cycle has a maximum during the winter of 30 to 35 ppb between June and August and a minimum during the summer (January to February) of 10 to 20 ppb. The surface O 3 mixing ratio during the summer was controlled by photochemical processes in the presence of sunlight, leading to the depletion process. During the winter, the photochemical production of surface O 3 was more dominant. The NOAA-AIRS and ECMWF-MACC analysis agreed well with the MASEC’16 data but twice were higher during the expedition period. Finally, the CO past data showed the surface O 3 mixing ratio was influenced by the CO mixing ratio over both the Ushuaia and Antarctic regions. Peak surface O 3 and CO hourly mixing ratios reached up to ~ 38 ppb (O 3 ) and ~ 500 ppb (CO) over Ushuaia. High CO over Ushuaia led to the depletion process of surface O 3 over the region. Monthly CO mixing ratio over Antarctic (South Pole) were low, leading to the production of surface O 3 over the Antarctic region.